Robotic Hand Solution for Impaired Hands - Zamel, Abdellatif; Prasetyo, Judhi (Master Program in Mechanical Engineering, Gunadarma University, 2024)
Hand disabilities can limit individuals from achieving the full range of finger movements seen in typical human hands, rendering some unable to grasp objects effectively. In response, this project introduces a portable 5 Degree of Freedom (DOF) robotic hand. It serves to amplify the limited flexion range of an impaired hand, expanding it to match the completely normal range of motion found in a robotic hand. This innovative solution is designed to attach to the palm of the impaired hand and is controlled by a glove equipped with five flex sensors. These sensors precisely measure the angles of finger bends and translate them into appropriate servo motor angles, facilitating enhanced dexterity for the user.